Constitutional Court Judges' Interpretation on the Limitation of Presidential and Vice-Presidential Term of Office: A Study of the Decision of the Constitutional Court Judge No. 117/PUU-XX/2022 - Dewi Iriani; Muhammad Fauzan; Esti Ningrum (Universitas Muhammadiyah Surakarta, 2023)
Purpose of the Study: This paper aims to analyze the philosophical meaning behind the Constitutional Court judges' interpretation of Decision No. 117/PUU-XX/2022 on the limitation of presidential and vice-presidential terms of office. It also aims to analyze the limitation of the presidential and vice-presidential term of office in the legal transformation and renewal in Indonesia. Methodology: This was normative research that used the qualitative method. The writer used the development law theory and judges’ interpretation and philosophical theory. Results: It was found that the Constitutional Court judges' interpretation of Decision No. 117/PUU-XX/2022 considered the grammatical interpretation, sociological interpretation, systematic interpretation, historic interpretation, comparative interpretation, and futuristic interpretation. In the legal transformation and renewal in Indonesia, the limitation of the presidential and vice-presidential term of office aims to create a checks and balances system among the state's high institutions. This limitation is already according to the 1945 Constitution. Applications of this Study: This research can motivate political parties to presidential and vice-presidential candidates that have integrity, morals, and character, as presidents and vice presidents can only serve for two periods. Thus, it is best to find the best candidates to serve the country. Novelty/Originality of this study: There has not been any previous research that analyzes Constitutional Court judges' interpretation of Decision No. 117/PUU-XX/2022 on the limitation of presidential and vice-presidential terms of office.